The Bawean communities of Gombak: a historical analysis of migration, social integration, and economic contributions - Mohd, Siti Hadija; Mansor Majdin, Mohamad Firdaus; Sulkafle, Mohamad Hazizie (Asian Scholars Network, 2025)
This study examines the historical development of the Bawean communities in Kampung Simpang Tiga and Kampung Sungai Cincin in the Gombak district of Selangor, Malaysia. This research looks at interviews from existing documentaries and other written sources to piece together the story of how the Bawean people moved from Bawean Island in Indonesia and settled in Gombak. It explores their journey, how they adapted to life in Malaysia, and the kinds of work they did throughout the 20th century. While Bawean communities have been present in Malaysia for over a century, their experiences are rather insufficiently documented in Malaysian historiography. This paper analyses selected interviews and published research to trace the ways in which Bawean settlers negotiated land, livelihoods, and identity within an evolving Malaysian socio-political framework. By using primary data collected by the research team in May 2024, which included personal communications and multiple forms of interviews with villagers of Kampung Sungai Cincin, Gombak, alongside available public video documentaries, secondary research, and public written sources, this study looks at how Bawean identity has stayed the same in some ways and changed in others, as part of the bigger story of migration in Southeast Asia.